Controlled Growth of Few‐Layer Hexagonal Boron Nitride on Copper Foils Using Ion Beam Sputtering Deposition. Issue 13 (3rd November 2014) - Wang, Haolin; Zhang, Xingwang; Meng, Junhua; Yin, Zhigang; Liu, Xin; Zhao, Yajuan; Zhang, Liuqi
<x xml:space="preserve">Abstract</x> Ion beam sputtering deposition (IBSD) is used to synthesize high quality few‐layer hexagonal boron nitride (h‐BN) on copper foils. Compared to the conventional chemical vapor deposition, the IBSD technique avoids the use of unconventional precursors and is much easier to control, which should be very useful for the large‐scale production of h‐BN in the future. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>